4(x+2)-3x+5=x+5

Simple and best practice solution for 4(x+2)-3x+5=x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+2)-3x+5=x+5 equation:


Simplifying
4(x + 2) + -3x + 5 = x + 5

Reorder the terms:
4(2 + x) + -3x + 5 = x + 5
(2 * 4 + x * 4) + -3x + 5 = x + 5
(8 + 4x) + -3x + 5 = x + 5

Reorder the terms:
8 + 5 + 4x + -3x = x + 5

Combine like terms: 8 + 5 = 13
13 + 4x + -3x = x + 5

Combine like terms: 4x + -3x = 1x
13 + 1x = x + 5

Reorder the terms:
13 + 1x = 5 + x

Solving
13 + 1x = 5 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
13 + 1x + -1x = 5 + x + -1x

Combine like terms: 1x + -1x = 0
13 + 0 = 5 + x + -1x
13 = 5 + x + -1x

Combine like terms: x + -1x = 0
13 = 5 + 0
13 = 5

Add '-13' to each side of the equation.
13 + -13 = 5 + -13

Combine like terms: 13 + -13 = 0
0 = 5 + -13

Combine like terms: 5 + -13 = -8
0 = -8

Simplifying
0 = -8

Combine like terms: 0 + 8 = 8
8 = -8 + 8

Combine like terms: -8 + 8 = 0
8 = 0

The solution to this equation could not be determined.

See similar equations:

| x^2+18x=-32 | | 10x+7+4x+7= | | x^2=-169 | | 6x^2+18x^2= | | -2x+30=7(x+3) | | (2x-1)+2(3x+7)=6x-3 | | 12(1/6-2/3x)-20/3(-3/4) | | 2.458+45+16.29= | | 3w+5w=48 | | 5*p=40 | | 0.24=0.42 | | 3x-5+2=8 | | -x-3y=-32x+3y=5 | | -24=5(u-8)-7u | | -32+2y=-6y | | 2s=34 | | 3w(w)-(w-5)(w-3)=2w(w)+1 | | f-16=-32 | | 18-3x=-15 | | 45x+9y=63 | | 0.18x+0.2(x-3)=0.01(4x-1) | | X+12y=-40 | | (x+7)(x+7)=-14 | | 16.40=x-0.20*x | | 0.5P-10=50-P | | -8-7(r-6)=90 | | d=5m | | 2+5x=6x-8 | | 17x+11=180 | | 18x+4=180 | | x-8=2x-14 | | 16.40=x-020*x |

Equations solver categories